Introduction of Anaerobic Co-Digestion Technology to Generate Liquid Biofertilizer for Developing Organic Agriculture in Lambeugak Village, Cot Glie, Aceh Besar - Darwin, Darwin; Yusmanizar, Yusmanizar (Institut Teknologi dan Bisnis Asia Malang, 2024)
Purpose: This community service aims to apply anaerobic co-digestion technology to produce liquid organic fertilizer. Method: This anaerobic co-digestion technology is carried out by combining two substrates including animal manure and agricultural residues in one anaerobic reactor. In principle, an anaerobic reactor will decompose liquid waste from livestock waste and solid waste from agricultural processes. A mixture of livestock waste and agricultural process waste that has been processed in an anaerobic reactor will be able to produce organic fertilizer. Practical Applications: This technology is applied not only to produce bio-fertilizer but also to introduce waste management practice among farmers by controlling environmental pollution. The pollution is typically caused by neglected livestock waste and burning residues resulted from agricultural processes. Conclusion: This practice may effectively generate liquid organic fertilizers from processing agricultural wastes anaerobically, and also could significantly reduce the environmental pollution caused by agricultural processes.